2015
DOI: 10.1007/s00404-015-3750-x
|View full text |Cite
|
Sign up to set email alerts
|

In-office transvaginal hydrolaparoscopy: a step-by-step, intraoperative pain evaluation

Abstract: Office THL seems to be well tolerated by patients. Chromosalpingoscopy was the least tolerated stage but it does not adversely impact on the procedure, which can be adequately accomplished by performing proper counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Comparing HSG to THL, THL is superior in diagnosing endometriosis and peritubal adhesions , whereas HSG gives more information about the uterine cavity. THL performed under local anesthesia is well-tolerated by the patient (Giampaolino et al 2015) and in two RCT's, THL patients were found to have lower pain scores than those undergoing HSG The most important aspect of tubal testing however, is its prognostic capacity: it has to distinguish between women who can conceive a natural pregnancy and women who have a strongly reduced chance to conceive, and therefore may need IVF or tubal surgery. Studies on the prognostic capacity of HSG showed that women with unilateral tubal patency compared to women with bilateral patent tubes had only a mild reduction in the chance of a natural conceived pregnancy, whereas women with bilateral tubal occlusion had a significantly reduced chance of a naturally conceived pregnancy (Verhoeve et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing HSG to THL, THL is superior in diagnosing endometriosis and peritubal adhesions , whereas HSG gives more information about the uterine cavity. THL performed under local anesthesia is well-tolerated by the patient (Giampaolino et al 2015) and in two RCT's, THL patients were found to have lower pain scores than those undergoing HSG The most important aspect of tubal testing however, is its prognostic capacity: it has to distinguish between women who can conceive a natural pregnancy and women who have a strongly reduced chance to conceive, and therefore may need IVF or tubal surgery. Studies on the prognostic capacity of HSG showed that women with unilateral tubal patency compared to women with bilateral patent tubes had only a mild reduction in the chance of a natural conceived pregnancy, whereas women with bilateral tubal occlusion had a significantly reduced chance of a naturally conceived pregnancy (Verhoeve et al 2011.…”
Section: Introductionmentioning
confidence: 99%